Pediatric head and neck injuries due to golf cart trauma. (September 2016) - Miller, Brandon; Yelverton, Eden; Monico, Jesus; Replogle, William; Jordan, J. Randall
Abstract: Introduction: Golf carts are increasingly used off the golf course and are often viewed as innocuous modes of transportation. However, research has shown they can cause significant injuries, particularly to children. Objectives: Analyze golf cart related head and neck injuries in children and adults from a national database. Methods: The National Electronic Injury Surveillance System (NEISS) was queried for golf cart injuries. The NEISS tracks consumer product related injuries from a sampling of approximately 100 emergency departments across the United States. Age, general diagnosis (concussion, fracture, laceration), body-part injured, disposition (hospitalized, discharged), location injury occurred, and mechanism of injury were analyzed. Results: Over an 11-year period, a total of 3433 total patients were identified. There were 1471 children (16 years old or younger), which compromised 42.9% of the cohort. Children were injured at home or on the road 44.7% of the time compared to only 16.6% of adults (p < 0.003). Children injured their head or neck 42.6% of the time compared to 28.6% of adults (p < 0.0001). Adults who were hit by a car while riding a golf cart or were ejected from the golf cart 44.6% of the time compared to 61.7% of children (p < 0.0001). There were 3.9% of children with a face, head, or neck fracture compared to only 2.4% of adults (p = 0.01). Conclusion: Children are more vulnerable to golf cart related injuries, specifically to the head and neck.